Perbandingan Hasil Belajar Kelas Eksperimen dan Kontrol Pembelajaran Sejarah Kebudayaan Islam di MTsN 5 Karawang - Sabrina Tegar Prihandini; Deni Lesmana; Salsabila Amarunnisa; Muhammad Samsul Jihad; Rina Nurpadilah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of implementing a certain learning model on student learning outcomes in the subject of Islamic Cultural History in class VIII MTsN 5 Karawang. The method used is a quasi-experiment with a posttest only control group design. The population of the study was all students of class VIII MTsN 5 Karawang in the 2025 academic year. The research sample consisted of one class, namely the experimental class that received treatment using the powerpoint learning model, and the control class that used the conventional learning model. The instrument used was a learning outcome test. The results of the study showed that there was a significant difference between student learning outcomes in the experimental class and the control class. This proves that the application of the powerpoint learning model can improve student learning outcomes.